Design of Mn-doped CdxZn1-xSe@ZnO triple-shelled hollow microspheres for quantum dots sensitized solar cells with improved photovoltaic performance. (15th May 2019) - Li, Zhen; Yu, Libo
Highlights: Multi-shelled ZnO hollow microspheres are controllable synthesized for QDSSC. Mn-Cdx Zn1-x Se QDs were formed on ZnO multi-shelled hollow microspheres. As shell numbers increase, light harvesting enhanced significantly. Mn-doping in QDs improves the electron injection and collection from QDs to ZnO. Abstract: Mn-Cdx Zn1-x Se@ZnO multi-shelled (including single-shelled, double-shelled, and triple-shelled) hollow microspheres (HMS) were successfully synthesized for application in quantum dots sensitized solar cell (QDSSC). The influence of shell numbers on photovoltaic performance of QDSSC were investigated. The results showed that larger surface area, repeated light reflection and reinforced light scattering can be achieved with triple-shelled HMS, which can improve light harvesting efficiency. Furthermore, midgap state created by Mn-doping in Cdx Zn1-x Se will facilitate electrons injection and collection from excited Cdx Zn1-x Se quantum dots (QDs) to ZnO. The multi-shelled effects and Mn-doping finally improve the short-circuit current (Jsc ) of Mn-Cdx Zn1-x Se@ZnO tripled-shelled HMS solar cell to 20.21 mA cm −2, leading to the power conversion efficiency significantly enhanced to 3.39%.